Factors associated with fear and anxiety in patients attending a dental care: A cross-sectional study - Alzate Zapata, Luisa María; Garcia Bran , Saira Yurany; Gaviria Correa, Isabella; López Sarmiento, Jonathan Smith; Ortiz Restrepo, Juliana; Franco Aguirre, John Querubín; Gallego Gómez, Clara Liliana (Revista Estomatología, 2021)
Background: People who feel fear and anxiety show worse oral health conditions than those who not, thus delaying dentist appointments to the point of cancelling all together.  Aim: Determine the degree of fear, anxiety and associated factors in patients seen in the clinics of the Faculty of Dentistry of the Universidad Cooperativa de Colombia.Materials and methods: A quantitative cross-sectional descriptive study was conducted with patients treated in clinics of the Faculty of Dentistry, for a universe of 941, a sample of 198 participants were calculated, not randomly selected. Three surveys were applied by the DFS (Dental Fear Survey), the MDAS (Anxiety Scale Modified Corah Dental) and a third survey to identify sociodemographic variables and factors associated with fear and anxiety.Results: The 92.4% of the participants presented some degree of fear in the dental practice. 48.7% have anxiety to some degree. The presence of fear and anxiety was found associated with the evaluation of previous experiences in dental practice (Vp